Isolation, identification, and characterization of potential biosurfactant-producing bacteria from processing wastewater for the development of eco-friendly green technology - Haneen I. Eldos (17632209) (2024)
Exploring novel biosurfactants (BS) has become a critical focus in biotechnology research. While BS provides eco-friendly substitutes to chemical surfactants, there is a need to identify high-potential BS-producing bacteria. Currently, the sustainable development of BS-based technologies is hindered by the lack of systematic exploration and understanding of microbial diversity for BS production. This study aims to isolate and identify novel BS isolated from different strains and elucidate their chemical structures for assessing their potential applications. Eleven BS-producing bacteria were isolated from processing wastewater (PWW). The strains were identified by 16S ribotyping and screened for BS production. The produced BS were characterized using Fourier transform infrared and nuclear magnetic resonance spectroscopic techniques. The results indicated that five strains produced a lipopeptide BS, while the other six strains produced glycolipid BS. According to the findings, eleven strains are distributed in eight genera indicating the high bacterial diversity in BS production. Other Information Published in: Bioresource Technology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biteb.2024.101763